The Effect Of Lemon (Citrus Limon L.) Extract On Mortality Of Aedes Sp. and Potential As Repellent - Suharno Zen; Agus Sutanto; Afiatur Rohmah (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2020)
Lemon (Citrus limon L.) is a plant with a peel type that contains phytochemical compounds namely flavonoids, terpenoids, tannins and limonenes that can be used as plant-based insecticides. The contents of these chemical compounds have the ability to kill mosquitoes, and act as respiratory poisons and stomach poisons for the mosquitoes. The purpose of this study was to determine the effect of the extract of lemon peel (Citrus limon L) On the mortality of Aedes sp. and to determine its potential as a repellent. This type of research used in thisstudy was an experiment using a completely randomized design study (CRD) which was carried out using 3 variations of the treatment dose of lemon peel extract (Citrus limon L) namely 25%, 27.5%, and 30%and controls (+) and (-). Data collection was carried out by looking at and recording mortality / deaths from Aedes sp. after being given treatment and observing mosquitoes on the body of mice and counting the number of mosquitoes that using the Protection Power formula. Data were statistically tested using One Way Anova and continued with LSD (Least Significant Difference) test. The results obtained by the value of Fcount ˃ table is 0.484 at the level of α = 0.05 so that H0 is rejected and H1 is accepted. This means that there is a significantinfluence of each treatment. The best effective dose is 30% with 50 mosquitoes dead. The highest protection power at a concentration of 30% was 97.3%, while the lowest protective power at a concentration of 25% was 77.1%.